Long-Term Survival of a Lynch Syndrome Patient With Eight Primary Tumors: A Case Report - Jiang, Jing; Huang, Ting; Lin, Xianlei; Zhang, Yu; Yang, Xuefei; Huang, Ling; Ye, Zhifeng; Ren, Xingchang; Teng, Lisong; Li, Jun; Kong, Mei; Lian, Liyan; et al. (Frontiers in Oncology, 2022)
With the modern technological developments in the diagnosis and treatment of cancer, the survival rate of cancer patients has increased. On the other hand, the incidence of multiple primary tumors is increasing annually. Lynch syndrome (LS), an autosomal dominant disorder with germline mutations in DNA mismatch repair genes, increases the risk of cancer in patients carrying those mutations. In this report, we present an extremely rare case of an 81-year-old male patient with eight primary malignancies and LS. The patient is still alive having survived for more than 41 years since the initial discovery of the first tumor. The eighth and most recently diagnosed primary cancer was a malignant peripheral nerve sheath tumor. Although there have been numerous reports of malignancies in LS, malignant peripheral nerve sheath tumors have not been reported previously with LS. Here, we report, to the best of our knowledge, the first case of a malignant peripheral nerve sheath tumor with LS.